Strong metal-support interaction for 2D materials: application in noble metal/TiB₂ heterointerfaces and their enhanced catalytic performance for formic acid dehydrogenation - Li, Renhong (2022)
Strong metal-support interaction (SMSI) is a phenomenon commonly observed on heterogeneous catalysts. Here, direct evidence of SMSI between noble metal and 2D TiB2 supports is reported. The temperature-induced TiB2 overlayers encapsulate the metal nanoparticles, resulting in core-shell nanostructures that are sintering-resistant with metal loadings as high as 12.0 wt%. The TiOx -terminated TiB2 surfaces are the active sites catalyzing the dehydrogenation of formic acid at room temperature. In contrast to the trade-off between stability and activity in conventional SMSI, TiB2 -based SMSI promotes catalytic activity and stability simultaneously. By optimizing the thickness and coverage of the overlayer, the Pt/TiB2 catalyst displays an outstanding hydrogen productivity of 13.8 mmol g-1 cat h-1 in 10.0 m aqueous solution without any additive or pH adjustment, with >99.9% selectivity toward CO2 and H2 . Theoretical studies suggest that the TiB2 overlayers are stabilized on different transition metals through an interplay between covalent and electrostatic interactions. Furthermore, the computationally determined trends in metal-TiB2 interactions are fully consistent with the experimental observations regarding the extent of SMSI on different transition metals. The present research introduces a new means to create thermally stable and catalytically active metal/support interfaces for scalable chemical and energy applications.